Особенности фенологии кровососущих комаров в связи с погодными условиями 1971—1972 гг - Шеремет, В.П. (Вестник зоологии, 1974)
﻿The results are presented of phenological observations for development of mosquitoes from the family Culicidae. Dynamics of population quantity and periods of development of preimaginal phases in mass species are established to depend on weather conditions.